Analisis Tingkat Keterampilan Teknik Dasar Pemain Bulutangkis PB Pemula Jaya Kota Jambi - Hidayatullah, Rahmat; Palmizal, Palmizal; Decheline, Grafitte (YASIN, 2025)
The fundamental skill of the overhead clear among athletes of PB Pemula Jaya in Jambi City remains suboptimal, as evidenced by errors in racket grip, body positioning, foot placement, and follow-through after striking the shuttlecock. This condition highlights the need for an analysis of athletes’ mastery of badminton’s basic techniques. The objective of this study is to analyze the level of basic technical skills of PB Pemula Jaya badminton players in Jambi City. The research employed a descriptive approach with a survey method. The study population comprised all athletes aged 15–17 years, totaling 16 individuals. The findings reveal that service skills in the very good category were demonstrated by 7 athletes (44%); lob skills in the fair category by 8 athletes (50%); dropshot skills in the fair category by 10 athletes (63%); and smash skills in the good category by 9 athletes (56%). These results indicate that the athletes’ mastery of basic badminton techniques remains varied, thereby necessitating a structured training program to enhance overall skill proficiency.